Experiences of Blogging About Visible and Long-term Skin Conditions: Interpretative Phenomenological Analysis - Selina K Tour; Andrew Thompson; Ruth A Howard; Michael Larkin (JMIR Publications, 2022)
BackgroundSkin conditions can detract from people's quality of life, much like conditions such as cancer, chronic pain, and depression. Visible skin conditions can lead to risk of stigmatization. It is acknowledged that there is a lack of available psychosocial support for people living with chronic skin conditions. One way in which individuals with long-term conditions are self-managing and providing peer support is through blogging and exchanging information on the web. To date, no research has specifically investigated how individuals with skin conditions experience the use blogging for self-management. ObjectiveThis study sought to investigate the experiences of individuals with visible, long-term skin conditions when blogging about their conditions. MethodsA systematic blog search and a short survey were used for recruitment. A total of 4 participants took part in email interviews, which were analyzed using interpretative phenomenological analysis (IPA). Skin conditions included alopecia, psoriasis, and hirsutism. The content of these individuals' blogs was also analyzed using a qualitative template method derived from the IPA analysis. ResultsThe interviews and accounts revealed a clear sense of uncertainty about the course of the bloggers' skin conditions. This appeared to be associated with feelings of distress and isolation, searching for treatments, and ultimately a sense of defeat. The data revealed that blogging provided a space where this sense of defeat was managed and challenged. Posting on the web facilitated connection with others and enabled support networks to be established that assisted in challenging the feelings of isolation experienced. The data demonstrate the important role that blogging played for these participants in developing a sense of acceptance of their condition. ConclusionsBlogging may provide a way for individuals to self-manage distress associated with visible skin conditions. It may provide similar benefits to those known to be derived from emotional disclosure that occurs during writing, with an added peer support dimension. Blogging has occurred naturalistically on web-based forums, and this study demonstrates how this form of interaction may warrant adaptation for use with web-based psychosocial interventions for people living with skin conditions. This study had a limited sample of 4 bloggers; therefore, further exploration would be needed to consider the utility of this approach.